ASCA-related antibodies in the blood sera of healthy donors and patients with colorectal cancer: characterization with oligosaccharides related to Saccharomyces cerevisiae mannan - Krylov, Vadim B.; Kuznetsov, Anton N.; Polyanskaya, Alina V.; Tsarapaev, Pavel V.; Yashunsky, Dmitry V.; Kushlinskii, Nikolay E.; Nifantiev, Nikolay E. (Frontiers in Molecular Biosciences, 2023)
Mannans are polysaccharide antigens expressed on the cell wall of different fungal species including Saccharomyces cerevisiae and Candida spp. These fungi are components of the normal intestinal microflora and the presence of antibodies to fungal antigens is known to reflect the features of the patient's immune system. Thus, titers of IgG and IgA antibodies against Saccharomyces cerevisiae mannan (ASCA) are markers for clinical diagnostics of inflammatory bowel diseases. The complex organization and heterogeneity of cell wall mannans may reduce the quality and reproducibility of ELISA results, due to interference by different antigenic epitopes. In this research, we analyzed the levels of IgG antibodies in the sera of healthy donors and donors with colorectal cancer using an array of synthetic oligosaccharides, related to distinct fragments of fungal mannan. This study aimed to establish the influence of oligosaccharide structure on their antigenicity. Variations in the structure of the previously established ASCA epitope (changing type of linkage, chain length, presence of branches) significantly modified the ability of ligands to bind circulating antibodies from blood sera. It was shown that surface presentation density of the ligand critically affects the results of enzyme immunoassay. The transition from natural coating antigens to the corresponding synthetic mimetics with a defined structure opens new opportunities for improving existing ELISA test systems, as well as developing diagnostic kits with new properties.